Explaining the Clinical Education Stressors in Nursing Students: A Qualitative Study - Kobra Ghorbanzadeh; Nastaran Ilka; Maryam Khoshbakht Pishkhani; Mojtaba Jafari; Hajar Sadeghi (Kerman University of Medical Sciences, 2023)
Background: Nurses are an important part of the health system, and the effectiveness of their clinical education has a significant impact on community health. The clinical environment is constantly changing, making student education very stressful. Due to the negative effects of stressors on education, the present study was conducted to explain the stressors in the clinical environment.Methods: In this qualitative study (content analysis), the participants were selected using the purposive sampling method. In-depth semi-structured interviews were conducted with 16 nursing students who had completed at least one semester of internship in Khalkhal University of Medical Sciences until data saturation was achieved. The data were coded, the related codes were classified into categories, and the main themes were extracted.Results: Four categories were obtained in this study: personal problems, the interaction between students and patients, patients' families, instructors, and ward staff, executive planning, and clinical education environment. The most important source of stress was personal problems, including a lack of awareness and fear of following some clinical guidelines. The lower-semester students were reported to have more stress than last-semester students.Conclusion: Due to the many clinical stressors, the related authorities should be required to promote students' professional development by identifying the clinical environment stressors and providing appropriate solutions to reduce and control them. In this regard, considering the role of instructors in reducing stress and facilitating student learning, providing educational programs to train instructors in this area can be one of the main steps to reduce student stress.